(untitled) (Tempo e Argumento, 2021)
This article gathers, using new readings, data and information that we have obtained in our research processes. Addressing history teaching in secondary school, fundamentally recent/present history (RPH), has enabled us to see the complex fabric between discipline, teaching, purposes, forms, and contents, all within the framework of changes produced at the glocal level. The text dialogues with historiographic, didactic, social, philosophical perspectives, in order to think about the new configurations of an era that challenge and stress history making and teaching practices. Also, it combines ideas that contribute to deepening didactic thinking about history, from a renewed perspective that makes it possible to address RPH through social issues (SIs) for citizenship education (CE) concerned with and sensitive about the world that people inhabit. Keywords: recent/present history; teaching; citizenship; social issues.